El estilo de liderazgo y el comportamiento organizacional del personal de la Empresa Contratista Inmaculada Virgen de la Puerta S.R.L. distrito de Trujillo 2013. - Polo Vidal, Roxana Cleopatra (2014)
This research work is mainly in order to determine the leadership style and how it affects organizational behavior contractor personnel Immaculate Virgin of the Gate SRL and propose strategies to improve organizational performance of contractor personnel. It stands as study variables: Independent Variable: The leadership style and, Dependent Variable: Organizational behavior of the contractor. - Deductive and hypothetical - deductive Inductive: descriptive design was used the following methods, as well. The study population consisted of 48 workers of the contractor, from which a sample with all the workers of the population was established, which is called the sampling frame. Was applied as a technique for data collection survey. By the results, we can see that the company Immaculate Virgin of the Gate SRL predominantly autocratic leadership style and use this to ensure that all products and / or services are produced in a consistent manner and the higher levels usually put many restrictions on creative ideas that may arise from the lower levels. In this research, a style of dynamic and flexible leadership is recommended, rather than a static one, which will allow the company Immaculate Virgin of the Gate SRL will overcome their weaknesses generating added value in their staff, and generate competitive advantage and place them on a waiting position among companies in its sector.